2018
DOI: 10.1155/2018/2972931
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of Nonlinear Flexural Behaviour of Lattice‐Web Reinforced Foam Core Composite Sandwich Panels

Abstract: This paper conducted experimental and numerical analysis of the nonlinear flexural behaviour of lattice-web reinforced foam core composite sandwich panels. Composite sandwich panels composed of a polyurethane (PU) foam core with glass fibre-reinforced polymer (GFRP) composites as the face sheets and lattice webs were fabricated through the vacuum infusion moulding process (VIMP). The flexural behaviour of these composite sandwich panels were experimentally investigated under both uniformly distributed and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Qi et al (2017) investigated the flexural behaviour of novel composite sandwich beams that feature a PAW or SOP wood core and GFRP face-skins reinforced with lattice-webs. Chen et al (2018) conducted experimental and numerical analysis of the nonlinear flexural behaviour of lattice-web reinforced foam core composite sandwich beams. Zhu et al (2018) investigated the bending behaviour of an innovative fibre reinforced polymer sandwich beam for application in a multistory building.…”
Section: Introductionmentioning
confidence: 99%
“…Qi et al (2017) investigated the flexural behaviour of novel composite sandwich beams that feature a PAW or SOP wood core and GFRP face-skins reinforced with lattice-webs. Chen et al (2018) conducted experimental and numerical analysis of the nonlinear flexural behaviour of lattice-web reinforced foam core composite sandwich beams. Zhu et al (2018) investigated the bending behaviour of an innovative fibre reinforced polymer sandwich beam for application in a multistory building.…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that the delamination usually occurred at the bonding interface between face sheets and core materials due to poor constraint of the foam core. Weiqing Liu, Hai Fang, et al [ 12 , 13 , 14 , 15 ] presented a kind of sandwich-latticed composite panel (SLCP) manufactured by vacuum-infusing resin process, as shown in Figure 1 . The lattice webs were added into the foam core to improve the peel resistance between face sheet and core surface.…”
Section: Introductionmentioning
confidence: 99%
“…In case of web-foam core structures (WFSs), a number of experimental and analytical studies have been performed. [34][35][36][37][38][39][40] Wang et al 35 reported that ultimate bending strength and initial bending stiffness of the web-foam core sandwich (WFS) panels could be enhanced by increasing the web thickness and web height under 4PB. Qi et al 36 studied on a two-way bending behaviour of WFS panel under conditions of four simply supported edges.…”
Section: Introductionmentioning
confidence: 99%